Supportive care for new cancer therapies. Issue 4 (July 2021) - Rapoport, Bernardo L.; Cooksley, Tim; Johnson, Douglas B.; Anderson, Ronald
Abstract : Purpose of review: The past decade has witnessed unprecedented delivery to the clinical arena of a range of novel, innovative, and effective targeted anticancer therapies. These include immunotherapies, most prominently immune checkpoint inhibitors, as well as agents that target growth factors and cancer-related mutations. Many of these new cancer therapies are, however, associated with an array of toxicities, necessitating insight and vigilance on the part of attending physicians to achieve high-quality supportive care alongside toxicity management. In this review, we consider some of the key supportive care issues in toxicity management. Recent findings: Although both supportive care and targeted therapies have brought significant benefits to cancer care, the management of novel cancer therapy toxicities is nevertheless often complex. This is due in large part to the fact that target organs differ widely, particularly in the case of checkpoint inhibitors, with minor dermatological disorders being most common, while others, such as pneumonitis, are more severe and potentially life threatening. Accordingly, efficient management of these immune-related adverse events requires collaboration between multiple medical specialists. Summary: Supportive care is a key component in the management of new cancer therapy toxicities and needs to be incorporated into treatment pathways.